In the article Current Research in Dental Sciences, 2024;34(4)-306-309 - Erratum E. (Current Research in Dental Sciences)
In the article Current Research in Dental Sciences, 2024;34(4)-306-309, the DOI number was inadvertently written incorrectly in the PDF file as 10.17567/currresdentsci.1555964, and the correct DOI number was recorded as 10.17567/currresdentsci.1556710 and edited on the web page.We apologize to our readers for this mistake.. 2024;34(4)-306-309, 10.17567/currresdentsci.1556710, 10.17567/currresdentsci.1555964